Examining evaporative demand and water availability in recent past for sustainable agricultural water management in India at sub-basin scale. (20th April 2022) - Singh, Vishal; Singh, Pushpendra Kumar; Jain, Sanjay Kumar; Jain, Sharad Kumar; Cudennec, Christophe; Hessels, Tim
Abstract: This study explores recent changes in evaporative demand and water availability across 100 river sub-basins in India by partitioning the actual evapotranspiration (AET) into green water evapotranspiration (ET-Green) and blue water evapotranspiration (ET-Blue). For computation of ET-Green and ET-Blue, the Budyko framework is applied to long-term scenario (2003–2017) and to intra-annual averaged series (i.e. 2003-2007, 2008–2012 and 2013–2017). For the Budyko analysis, the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS), Global Land Data Assimilation System (GLDAS) AET and Climate Research Unit Global Data Assimilation System (CRU GDAS) Potential ET (PET) climate forcing variables have been utilized. Multiple hydro-climatic indicators, such as dryness index (DI), evaporative index (EI), and responsivity with respect to theoretical Budyko curve are computed and they show substantial variations across sub-basins from far past time (2003) to recent past (2017). The changes in DI and EI highlight the diversity in evaporative demand and dryness condition across the country. Results reveal that India's evaporative water demand is largely influenced by ET-Green (up to 65%) that depends mainly on precipitation. At the same time, in many river sub-basins, ET-Blue that depends on external sources of water like diversion or stored water, is significant. The shape parameter (ω) of Fu's Budyko equation, that can be utilized for the future assessment of ET-Green and ET-Blue, has been optimized. The results of this study would of immense value for sustainable irrigation water management and improving water use efficiency in agriculture and overall water availability in river basins in India. Graphical abstract: Image 1 Highlights: Implemented Budyko framework to assess the India's evaporative water demand and availability at sub-basin level. Characterized evaporative water in terms of ET-Green and ET-Blue fractions at sub-basin. Assessed changes in Budyko based indicators like EI and DI for different recent past time slices. Computed shape parameter 'ω' of Fu's Budyko equation for the future assessment of ET-Green and ET-Blue.